Drinking, Identity, and Practice: Becoming Inca at Purun Llacta de Soloco (Chachapoyas) - Risco, Lorenzo; Crandall, James M. (Journal of Global Archaeology, 2025)
This article examines two silver vessels (aquillas) from the Early Colonial Period, discovered in a ritual context at the archaeological site of Purun Llacta de Soloco (Chachapoyas, Peru). These aquillas feature eight graphic scenes represented in a realistic style. This pair of objects is analyzed here from the perspective of nonverbal communication to identify the message they conveyed. An assessment of the material condition and agentive substance of the aquillas suggests that toasting among authorities, ancestors, and deities reaffirmed the sociopolitical relationships of Purun Llacta. Furthermore, we consider how these vessels functioned as a medium of political communication, by which elites at Purun Llacta expressed the adoption of a new identity and its maintenance into the Spanish colonial period.